Estimating Long‐Run Incarceration Rates for Australia, Canada, England and Wales, New Zealand, and the United States. (1st April 2020) - Leigh, Andrew
Abstract : Compiling data from dozens of archival sources, I assemble the most extensive series to date of the long‐run imprisonment rate for five English‐speaking nations: Australia, Canada, England and Wales, New Zealand, and the United States. These series are constructed as a share of adults rather than the entire population, and I discuss why the latter can be misleading. In the late‐nineteenth century, Australia had the highest incarceration rate of these nations. Today, the United States has the highest rate. With the exception of Canada, incarceration rates have risen markedly since the mid‐1980s. These new series are made available in full, to allow other researchers to explore the consequences and causes of incarceration.